PENGARUH KONSENTRASI DAN LAMA PERENDAMAN BAHAN DENGAN ASAM LAKTAT SEBELUM PENGERINGAN TERHADAP KARAKTERISTIK BUBUK BUNGA KENIKIR (Tagetes erecta L.) - Nadaiswara Putra, Made Wahyu; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): Maret, 2019)
Marigold flowers (Tagetes erecta L .)  have the potential as natural dyes that contain color pigments from carotenoid compounds. The purpose of this study was to determine the effect of lactic acid concentration and soaking time before drying on the characteristics of kenikir flower powder and determine the concentration of lactic acid and the duration of lactic acid immersion before the best combustion to produce kenikir flower powder. This study used a randomized block design using factorial patterns with 2 factors. The first factor is the concentration of lactic acid consisting of 3 levels: 0,5, 1,0, and 1,5%. The second factor is the immersion time consisting of 3 levels: 60, 90, and 120 minutes. The results showed that the treatment of lactic acid concentration affected the total carotenoid level, brightness (L *), redness level (a *) yellowish level (b *) but did not significantly affect the water content. The treatment of immersion time did not affect the total carotenoid level, brightness level (L*), yellowish level (a*), redness level (b*) and water content. Immersion treatment with a concentration of 1,5% and 90 minutes soaking time is the best treatment for producing kenikir flower powder with characteristics namely water content 16,71%, total carotenoid content 18,77%, brightness level (L*) 38,23, redness level (a*) 29,02, yellowish level (b*) 51,93. Keywords : Tagetes erecta L ., lactic acid, karotenoid, color